2006
DOI: 10.1203/01.pdr.0000228319.10481.ea
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity of the Human Newborn Is Polarized Toward a High Ratio of IL-6/TNF-α Production In Vitro and In Vivo

Abstract: Human newborns are susceptible to microbial infection related to incompletely defined aspects of the neonatal immune system. To characterize neonatal innate immunity, we studied production of two early response cytokines in response to Toll-like receptor (TLR)-activating microbial stimuli in vitro: the proinflammatory cytokine tumor necrosis factor (TNF)-␣ and IL-6, a multifunctional cytokine with antiinflammatory and Th2-polarizing properties. Neonatal cord blood responses to multiple TLR agonists, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
143
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 25 publications
15
143
0
9
Order By: Relevance
“…We subsequently investigated the effects of activin-A in LPS-induced responses by neonatal peripheral blood monocytes that express enhanced levels of the LPS receptor, toll-like receptor-4, and respond highly to this stimulus (1,(19)(20)(21). Our findings demonstrated that LPS induced a dramatic increase in the production of IL-1β (P < 0.01), IL-6 (P < 0.01), CXCL8 (P < 0.01), and IL-10 (P < 0.01) by neonatal peripheral blood monocytes, as compared with nonstimulated cells (Figure 5a-d).…”
Section: Activin-a Suppresses Inflammatory Cytokine and Chemokine Relmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently investigated the effects of activin-A in LPS-induced responses by neonatal peripheral blood monocytes that express enhanced levels of the LPS receptor, toll-like receptor-4, and respond highly to this stimulus (1,(19)(20)(21). Our findings demonstrated that LPS induced a dramatic increase in the production of IL-1β (P < 0.01), IL-6 (P < 0.01), CXCL8 (P < 0.01), and IL-10 (P < 0.01) by neonatal peripheral blood monocytes, as compared with nonstimulated cells (Figure 5a-d).…”
Section: Activin-a Suppresses Inflammatory Cytokine and Chemokine Relmentioning
confidence: 99%
“…Isolated monocytes were cultured in Roswell Park Memorial Institute medium with GlutaMAX (Invitrogen) supplemented with 2% penicillin/streptomycin (Sigma-Aldrich) at 37 °C, 5% CO 2 for 4, 24, or 48 h in the presence or absence of LPS (1 μg/ ml; Sigma-Aldrich), as previously described (22). We used LPS to examine the effects of activin-A on responses mediated by neonatal monocytes, as these cells express high levels of the LPS receptor, tolllike receptor-4, on their surface and respond highly to this stimulus (1,(19)(20)(21). Moreover, LPS stimulation closely resembles monocyte activation with bacterial stimuli (1).…”
Section: In Vitro Stimulation Of Neonatal Peripheral Blood Leukocytesmentioning
confidence: 99%
“…Erythema toxicum neonatorum, which manifests as rash and fever in term neonates (21,22) is thought to result from a inflammatory response to SE bacteria that penetrate the dermis via hair shafts (23). Furthermore, IL6 levels significantly increase during the first weeks of life in noninfected term neonates, possibly reflecting immune recognition of initial colonization with commensal bacteria such as SE (24). Although all neonates are ubiquitously colonized with SE within days after birth (18), erythema toxicum neonatorum is exceptionally rare in preterm infants (21), suggesting significant GA-related differences in innate immune responses in vivo.…”
Section: Monocyte Surface Expression Of Tlrsmentioning
confidence: 99%
“…Whether and how the innate immune response in neonates contributes to their susceptibility to infection or TLR stimulation is still controversial. In human, it has been reported that mononuclear cells from cord blood secrete lower amounts of TNF than those from healthy adults in response to TLR agonists (10)(11)(12)(13), whereas other studies draw opposite conclusions (14)(15)(16). Results from studies in mice also conflict because neonates produce either lower (17,18) or higher (19) levels of TNF compared with adults.…”
mentioning
confidence: 99%